Strategic orientation, business model innovation and corporate performance—Evidence from construction industry - Han, Wucheng; Zhou, Yang; Lu, Ruoyu (Frontiers in Psychology, 2022)
In the highly competitive Chinese construction market, developing a strategic orientation alone fails to maintain the sustainable competitive advantage of firms. In this paper, the mechanism of strategic orientation and business model innovation on corporate performance in a dynamic environment is investigated. Based on a sample of 356 Chinese construction firms, the partial least squares structural equation modelling (PLS-SEM) was adopted to test the hypotheses. It is found that entrepreneurial orientation and market orientation affect corporate performance differently. Unlike market orientation, which directly affects corporate performance, entrepreneurial orientation through business model innovation exerts influence instead of direct affection. Business model innovation plays a fully mediating role between entrepreneurial orientation and corporate performance and partially between market orientation and corporate performance. Meanwhile, environmental dynamism can positively moderate the relationship between business model innovation and corporate performance. This paper deepens the research on strategic orientation, business model innovation and corporate performance. The findings can provide a reference for construction firm managers to develop strategies and conduct business model innovation, which can finally help seek sustainable development in a dynamic environment.